Does the use of a foreign language influence attention and genre-specific viewing patterns for job advertisements? An eye-tracking study. Issue 6 (November 2016) - Hilberink-Schulpen, Béryl; Nederstigt, Ulrike; van Meurs, Frank; van Alem, Emmie
Abstract: The aim of this online experiment was to find evidence for both the alleged attention-getting function of the use of L2 English in job advertisements and for a possible genre–specific viewing pattern for job advertisements. A mixed design eye–track experiment among 30 native speakers of Dutch who saw all-Dutch and mixed Dutch– English job advertisements tested whether the use of foreign language English in Dutch ads changed the viewing pattern compared to all-Dutch job advertisements. That is, it investigated whether the use of a foreign language attracted more attention (in terms of first fixation, number and duration of fixations, and returned views), and altered the genre–specific viewing pattern for job ads. Overall, no evidence for the attention–getting ability of foreign language use in jobs ads was found. On the contrary, English used in the company information seemed to have a deterring effect. Support was found for a genre–specific viewing pattern for job ads, which, however, was not altered by the use of a foreign language. Our results suggest that use of English is not necessarily a good option to attract attention. Findings for genre-specific viewing patterns suggest that makers of job ads should make the job description as attractive as possible, since this is the first element viewed. This is the first online study to investigate the effect of language choice on attention in job ads and the viewing patterns specific to this ad genre.